Genotype-phenotype variability in Chinese cases of Treacher Collins syndrome. (3rd July 2019) - Li, Xiaohong; Su, Yu; Huang, Shasha; Gao, Bo; Zhang, Dejun; Wang, Xiaobin; Gao, Qin; Pang, Hong; Zhao, Yan; Yuan, Yongyi; Dai, Pu
Abstract: Background: Treacher Collins syndrome (TCS) is a clinically and genetically heterogeneous disorder of craniofacial development mainly caused by variants in TCOF1, POLR1D, and POLR1C . Objectives: This study examined the causative genes of five TCS cases. Materials and Methods: In this study, two familial cases and three sporadic cases clinically diagonsed with TCS are described. Mutational analysis in probands was performed by targeted next-generation sequencing (NGS). Mutations identified by NGS were further confirmed by Sanger sequencing or multiplex ligation-dependent probe amplification (MLPA). Results: A novel gross deletion (exons 9–13), a novel small deletion (c.381_382delAG), and two known deletions (c.4131_4135delAAAAG and c.2394_2395delAG) within TCOF1 as well as a known mutation (c.91C > T) in POLR1D were identified. These five cases exhibited high inter- and intra-familial phenotypic heterogeneity. Conclusion: This is the first report of Chinese TCS cases caused by a gross deletion within TCOF1 and mutations in POLR1D . In addition to expanding the spectrum of TCS-associated mutation in the Chinese population, our findings present the diversity of its clinical presentation. It is recommended that analyses such as NGS or MLPA capable of detecting large deletions be undertaken as a part of TCS molecular diagnosis.